Digital Transformation of Rice Supply Chain: A Systematic Literature Review Towards Traceability-Based Digital Business Ecosystem - Teguh Mizwarni Anugrah; Azrifirwan; Kiki Yulianto (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Classic issues in Indonesia's rice agro-industry supply chain include fragmented distribution channels, price volatility, and a lack of quality assurance (traceability) for consumers. While there are several digital solutions out there, including agricultural e-commerce and QR Code-based tracking systems, the majority of these solutions are operating in silos. This article reviews the state of the art of digital technologies for rice commodities and proposes a framework based on Digital Business Ecosystem (DBE). Building on a Systematic Literature Review (SLR) of 20 selected studies (2016-2025), the research highlights three main trends: (1) the predominance of e-commerce platforms oriented towards final sales, (2) the establishment of technical traceability systems that are not yet market-integrated, and (3) poor adoption of ecosystem strategies. A unified digital ecosystem integration between production management systems (on-farm), quality validation (traceability), and market platforms (marketplaces) is deemed to be crucial for enhancing competitiveness among producers, while also securing consumer trust. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and Production